2019
DOI: 10.1021/acs.jafc.8b07304
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-Candida Effects of Brazilian Organic Propolis, a Promising Source of Bioactive Molecules and Functional Food

Abstract: Brazilian organic propolis (BOP) is an unexplored Brazilian propolis that is produced organically and certified according to international legislation. Our results showed that BOP has strong anti-inflammatory effects and acts by reducing nuclear factor κB activation, tumor necrosis factor α release, and neutrophil migration. In addition, BOP6 exhibited antifungal activity on planktonic and biofilm cultures of Candida albicans, Candida glabrata, Candida tropicalis, Candida krusei, and Candida parapsisolis and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 69 publications
0
31
0
3
Order By: Relevance
“…The Unexplored Brazilian Organic Propolis -BOP6 crude extract was characterized as an anti-inflammatory and antibiofilm agent. It reduces the mortality rate by 30% in C. albicans infected sample with MIC ranging from 50 to 100 µg/mL while in combination with Amphotericin B, it decreases to 0.25 to 1.0 µg/mL (Nani et al, 2019). Through library screening with the information regarding fungal extract, it was revealed that Bionectria ochroleuca, an endophytic fungus.…”
Section: Natural Extracts and Essential Oilsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Unexplored Brazilian Organic Propolis -BOP6 crude extract was characterized as an anti-inflammatory and antibiofilm agent. It reduces the mortality rate by 30% in C. albicans infected sample with MIC ranging from 50 to 100 µg/mL while in combination with Amphotericin B, it decreases to 0.25 to 1.0 µg/mL (Nani et al, 2019). Through library screening with the information regarding fungal extract, it was revealed that Bionectria ochroleuca, an endophytic fungus.…”
Section: Natural Extracts and Essential Oilsmentioning
confidence: 98%
“…In another study, when gold nanoparticles (Au-NP) were tested on the biofilms formed due to C. albicans, these particles showed robust inhibitory activity. Additionally, these Au-NPs increased the host immune response activity against these pathogenic organisms (Yu et al, 2016;Nani et al, 2019). From previous studies, chitostan and its nanoparticle (ChNPs) were already known for their antifungal property (Ing et al, 2012;Mohammed et al, 2017;Gondim et al, 2018).…”
Section: Recent Advances To Inhibit C Albicans Biofilm Formationmentioning
confidence: 99%
“…Esta própolis, pouco estudada, tem chamado a atenção devido a seu sabor suave e fortes atividades biológicas, tais como antioxidante, anti-inflamatória e antimicrobiana (TIVERON et al, 2016). Estudos com as própolis orgânicas do sul do país mostraram a existência de 7 perfis cromatográficos distintos (PO1-PO7) (TIVERON et al, 2016), e uma grande diversidade de fitoquímicos (NANI et al, 2020). Devido à grande variedade de plantas no ambiente em que as colmeias estão inseridas, a origem botânica dessas própolis ainda é pouco conhecida (TIVERON et al, 2020).…”
Section: 1 221 Própolis Orgânicaunclassified
“…Estudos têm sido feitos para a determinação da dose letal que mata 50% dos organismos (DL 50 ) de extratos de frutas e própolis, o que possibilita a extrapolação dos resultados obtidos para valores em humanos (DA CUNHA et al, 2020;LAZARINI et al, 2018;NANI et al, 2020;SOARES et al, 2019). Deste modo, a adoção do modelo experimental com G. mellonella tem se mostrado promissor para ensaios in vivo que resultem em dados relevantes para as pesquisas de toxicidade de alimentos.…”
Section: 5 25 Biodisponibilidade Bioacessibilidade E Bioatividadeunclassified
See 1 more Smart Citation